Problems in Functioning in Patients with Chronic Musculoskeletal Pain Admitted for Multidisciplinary Rehabilitation. Issue 6 (30th July 2015) - Meesters, Jorit J.; Volker, Gerard; Koele, Robin; van Gestel, Marc C.; Smeets, Rob J.; Vliet Vlieland, Thea P.
Abstract: Background: Little is known about the extent to which improvements in various problem areas are attained after multidisciplinary rehabilitation program in patients with chronic musculoskeletal pain (CMP). Aim: To describe the pre‐ and postcontents of problems in functioning from the Canadian Occupational Performance Measure (COPM) in terms of the International Classification of Functioning, Disability and Health (ICF) in CMP patients following a 15‐week rehabilitation program. Methods: In all patients admitted to a rehabilitation program, the COPM was administered at admission and discharge. The problems identified at admission were linked to ICF chapters using an established linking procedure. Changes of COPM Performance/Satisfaction scores (1–10; low–high) with 95% confidence intervals (CIs) were calculated, and effect sizes (ESs) were computed. Results: In total, 165 patients were included with a mean age of 44.1 (SD 12.9) years; among them, 143 (87%) were women. At admission, totally 801 problems were identified and linked to 706 unique ICF categories: 83 (12%) were related to the ICF component "Body Functions" and 621 (88%) to "Activities and Participation". ICF chapters "d4 Mobility" (124, 18%) and "d9 Community social and civic life" (143, 20%) were most frequently identified. The median changes of the COPM total scores for Performance and Satisfaction were 2.1 (95% CI 1.9 to 2.3, ES: 1.75) and 3.2 (95% CI 2.9 to 3.4, ES: 2.38). Conclusion: A 15‐week multidisciplinary treatment program showed that most problems were seen within chapters Mobility and Community life of the ICF. The program led to significant improvements of patient reported problems, the magnitude of which was similar for all different problem areas.